Evaluation of Online Inquiry Competencies of Chilean Elementary School Students: A Dataset - Gonzalez-Ibanez, R; Chourio-Acevedo, L (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In the age of abundant digital content, children and adolescents face the challenge of developing new information literacy competencies, particularly those pertaining to online inquiry, in order to thrive academically and personally. This article addresses the challenge encountered by Chilean students in developing online inquiry competencies (OICs) essential for completing school assignments, particularly in natural science education. A diagnostic study was conducted with 279 elementary school students (from fourth to eighth grade) from four educational institutions in Chile, representing diverse socioeconomic backgrounds. An instrument aligned with the national curriculum, featuring questions related to natural sciences, was administered through a game named NEURONE-Trivia, which integrates a search engine and a logging component to record students’ search behavior. The primary outcome of this study is a dataset comprising demographic information, self-perception, and information-seeking behaviors data collected during students’ online search sessions for natural science research tasks. This dataset serves as a valuable resource for researchers, educators, and practitioners interested in investigating the interplay between demographic characteristics, self-perception, and information-seeking behaviors among elementary students within the context of OIC development. Furthermore, it enables further examination of students’ search behaviors concerning source evaluation, information retrieval, and information utilization. Dataset: The dataset is available in the Mendeley Data repository. Doi: 10.17632/dwkh4yfm7f.4. Dataset License: The license under which the dataset is made available is CC-BY 4.0 © 2024 by the authors.